Determinants of Foreign Technological Activity in German Regions – A Count Model Analysis of Transnational Patents (1996-2009) - Eva Dettmann; Iciar Dominguez Lacasa; Jutta Günther; Björn Jindra (Leibniz-Institut für Wirtschaftsforschung Halle (IWH), 2013)
This paper analyses the determinants of spatial distribution of foreign technological activity across 96 German regions (1996-2009). We identify foreign inventive activity by applying the 'cross-border-ownership concept' to transnational patent applications. The descriptive analysis shows that foreign technological activity more than doubled during the observation period with persistent spatial heterogeneity in Germany. Using a pooled count data model, we estimate the effect of various sources for externalities on the extent of foreign technological activity across regions. Our results show that foreign technological activity is attracted by technologically specialised sectors of regions. In contrast to existing findings this effect applies both to foreign as well as domestic sources of specialisation. We show that the relation between specialisation and foreign technological activity is non-linear and that it is influenced by sectoral heterogeneity. Externalities related to technological diversification attract foreign R&D only into 'higher order' regions. – – Der Beitrag analysiert die Determinanten der räumlichen Verteilung ausländischer technologischer Aktivitäten in Deutschland im Zeitraum von 1996 bis 2009. Um ausländische technologische Aktivitäten auf regionaler Ebene (96 Regionen) zu identifizieren, wird das Konzept der cross-border-ownership auf transnationale Patente angewendet. Die deskriptive Auswertung zeigt, dass sich ausländische technologische Aktivitäten in Deutschland im Betrachtungszeitraum verdoppelt haben. Dabei ist die räumliche Verteilung an sich sehr heterogen und verändert sich über die Zeit kaum. Im Zentrum der Analyse der Determinanten der räumlichen Verteilung stehen verschiedene Formen der Externalitäten (spillovers), insbesondere industrielle Spezialisierung (Marshall) und Diversifizierung (Jacobs) sowie potenzielle science-industry spillovers. Die Schätzungen des negativen Binominalmodells zeigen, dass Spezialisierung (intraindustry spillovers) und science-industry spillovers einen positiven Effekt auf ausländische technologische Aktivitäten haben. Diversifizierung (inter-industry spillovers) hingegen zeigt positive Effekte auf ausländische technologische Aktivität nur in so genannten 'Regionen höherer Ordnung'.
urn:nbn:de:gbv:3:2-23117
Keywords: O32; O33; R12; 330; foreign direct investment; technology; Europe; patent data